SOUTHEAST ASIA ECONOMIC DEVELOPMENT THROUGH ASEAN REFORM - Lue Estherina Flora Tanti (International Law Department, Faculty of Law Universitas Padjadjaran, 2019)
Abstract Since its establishment, Association of Southeast Asia Nations (ASEAN) has achieved many accomplishments in economic sectors including regional trade and connectivity. However, ASEAN’s work as a bloc has remained complacent and ineffective causing insignificant results. In fact, this was caused by the deeply rooted key norm guiding the ASEAN’s behaviour, the ASEAN Way. This ASEAN Way which mostly involved sovereignty and non-interference could be argued as the factor maintaining the stability in the region, yet at the same time it might also be considered as the barrier to the regional economic development. Throughout the years, the world is changing and so is ASEAN. This change indicates that there is inconsistency between the aims, the provisions, and the implementation and it is time to take a closer look again at the Association. Therefore, this article is focusing at the intersection between economics and legal frameworks in the regional organization, which remains relatively unexplored territory. It will analyse past actions of ASEAN and European Union as comparison. Several approaches will be considered before eventually proposing the best form of reform for ASEAN and its citizens. Keywords: ASEAN Reform, Economic Development, Regional Organization AbstrakSejak awal dibentuknya Association of Southeast Asia Nations (ASEAN), ASEAN telah meraih berbagai pencapaian dalam bidang ekonomi termasuk dalam bidang perdagangan dan hubungan regional. Akan tetapi, sebagai sebuah blok, ASEAN masih kurang efektif dalam menangani permasalahan regional yang menghasilkan hasil yang tidak signifikan. Faktanya, hal ini disebabkan norma yang tertanam sebagai landasan tindakan ASEAN, the ASEAN Way. ASEAN Way ini sangat melibatkan prinsip kedaulatan dan non-intervensi yang merupakan faktor dari stabilitas di ASEAN, namun secara bersamaan juga merupakan hambatan dalam perkembangan ekonomi regional. Seiring berkembangnya zaman, dunia berubah tidak terkecuali ASEAN. Perubahan dalam ASEAN ini mengindikasi bahwa tujuan, peraturan dan implementasi ASEAN tidak konsekuen dan membutuhkan peninjauan kembali. Oleh karena itu, peneltian anilitis yuridis ini menfokuskan pada percabangan antara ekonomi dan peraturan hukum dalam organisasi regional, yang kurang tereksplor. Penelitian ini juga akan menganalias tindakan ASEAN di masa lalu dan membandingkan dengan Uni Eropa. Beberapa pendekatan akan dipertimbangkan sebelum diajukannya bentuk reformasi yang terbaik untuk ASEAN dan seluruh warganya. Kata Kunci: Organisasi Regional, Perkembangan Ekonomi, Reformasi ASEAN